Poetry of the Resistance, Resistance of the Poet - Yasmine Getz (Studies in 20th & 21st Century Literature, 2002)
The expression "French Resistance poetry" tends to immediately suggest a poetry written for an audience belonging to a specific historical period, namely that stretching from 1940, the time of the French defeat and collaboration, to 8 May 1945, the date of the Allied Victory over Nazism...
Keywords: French Resistance poetry; audience; 1940; French defeat; collaboration; 8 May 1945; Allied Victory over Nazism